If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + 6) + -35 = 0 Reorder the terms: 8(6 + x) + -35 = 0 (6 * 8 + x * 8) + -35 = 0 (48 + 8x) + -35 = 0 Reorder the terms: 48 + -35 + 8x = 0 Combine like terms: 48 + -35 = 13 13 + 8x = 0 Solving 13 + 8x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 8x = 0 + -13 Combine like terms: 13 + -13 = 0 0 + 8x = 0 + -13 8x = 0 + -13 Combine like terms: 0 + -13 = -13 8x = -13 Divide each side by '8'. x = -1.625 Simplifying x = -1.625
| 2x-3x+4=3 | | 2a+3b=58 | | 4log(2x-3)=14 | | (ab+a+b+6)+(3ab-b+c-6)= | | 4x^2+2x+15=0 | | 16t^2+40t+6=0 | | 64=20x-x^2 | | 2.5x+1.7=7.4e | | 3x-1-x-3=2 | | 2X-4X-4=10 | | (3x+7)(x-4)x=0 | | 1zx(1b+5a)= | | 7=ab-cb-3 | | 100x+50y=0 | | 7x-2=-2-19 | | 3m(m-2)=0 | | X^5+5=-27 | | x^2+y^2+6x-8y+5=0 | | ab+a+b+6+3ab-b+c-6= | | 6(2x-7)=33 | | x^5+5ifx=-2 | | 32x^2+32x-1=0 | | 9q-(7q+12)=6-(2q-7) | | (3a+2)(3a-1)=0 | | 3a+2=3a-6 | | -5+(-15d+1)=2(7d-17)-d | | .07x+.03y=366 | | 5m+6km-8hm=m | | 15-4x=45+10x | | 8s^2-9s+2=0 | | d^2-18d+81=13 | | 5m+6km-8hm= |